Implementasi Pendidikan Integratif dalam Pembentukan Karakter Insan Kamil di Pesantren Mahasiswa An Najah Purwokerto - Lutfiana, Annisa; Fauzi, Fauzi (YASIN, 2024)
Integrative education is an approach that combines various disciplines and skills to shape individuals who are balanced intellectually, morally, and socially. This research aims to explore the implementation of integrative education in the character formation of kamil individuals at the An-Najah Student Islamic Boarding School in Purwokerto. The method used in this research is a qualitative approach with techniques such as in-depth interviews, observation, and documentation study. The research sample consists of caregivers, teachers, and students of the An-Najah Student Islamic Boarding School in Purwokerto. The collected data were analyzed using thematic analysis techniques to identify the application of integrative education in the formation of kamil human character. The research results show that the implementation of integrative education at An-Najah Student Islamic Boarding School includes strengthening the aspects of spirituality, religiosity, entrepreneurship, and leadership. In addition, programs such as Quranic studies, leadership training, entrepreneurship, and habituation to interacting with the surrounding community contribute to shaping the character of students who are virtuous, responsible, and ready to contribute to social life. In conclusion, the integrative education implemented at Pesantren Mahasiswa An-Najah Purwokerto has proven effective in shaping the character of a balanced insan kamil, harmonizing intelligence, morality, and social skills.